Clinical and ultrasonographic evaluations of the shoulders of elite swimmers - Rodeo, S. A.; Nguyen, J. T.; Cavanaugh, J. T.; Patel, Y.; Adler, R. S. (The American Journal of Sports Medicine, 2016)
Background: Shoulder pain is a common problem in competitive swimmers, but the structural alterations in elite-level competitive swimmers are not well known. Hypothesis: Adaptive changes are common in the rotator cuff, bursa, labrum, and capsule in elite swimmers, and such abnormalities are related to factors concerning training and correlate with symptoms. Study Design: Cross-sectional study; Level of evidence, 3. Methods: The study population was the 2008 United States Olympic swimming team. All athletes completed standardized scales on shoulder pain and function and provided data on their training history and history of shoulder pain or injuries. Each athlete also underwent a comprehensive physical examination of both shoulders, followed by an evaluation of the rotator cuff, biceps, and bursa using ultrasound with dynamic images to assess for subcoracoid impingement and subacromial impingement. Results: A history of shoulder pain was reported by 29 of 42 (66%) athletes. Morphological changes consistent with tendinosis were common in the biceps (33/46 shoulders; 72%) and supraspinatus/infraspinatus (44/46 shoulders; 96%). Subcoracoid impingement was seen in 17 of 46 shoulders (37%), with subacromial impingement seen in 34 of 41 shoulders (83%). There was an increased odds ratio (OR) for biceps tendinosis in older swimmers (OR, 1.92; 95% CI, 1.23-3.00; P = .004) and in swimmers who had missed a competition because of shoulder pain (OR, 9.76; 95% CI, 1.13-84.3; P = .038). There was an increased OR for rotator cuff tendinosis in swimmers who reported worse scores for pain with activities (OR, 0.10; 95% CI, 0.01-0.78; P = .028) and in those with a positive sulcus sign (OR, 33.2; 95% CI, 3.09-355; P = .004). There was an increased OR for impingement in swimmers with a positive sulcus sign (OR, 5.40; 95% CI, 0.80-36.3; P = .083), worse pain scores (OR, 0.44; 95% CI, 0.22-0.87; P = .019), and a partial rotator cuff tear (OR, 31.2; 95% CI, 3.58-272; P = .002). Conclusion: We found a high prevalence of rotator cuff and biceps tendinopathy, which was associated with increased symptoms. Tendinosis was also more common in swimmers with a positive sulcus sign, suggesting a role for shoulder laxity.